A Brief Mapping of Theory and Evidence of Investors’ Behavioural Biases - Mangala, Deepa; Sharma, Mamta (Indian Journal of Finance, 2014)
Investment decision making focuses on how investors make decisions to buy or sell securities. What guides their choices among alternatives, what are their investment objectives, constraints, and risk profile; and ultimately, what influences their decision making during the stock selection process. Behavioural finance deals with the psychology of the investor. It tries to explain how an investor makes an investment decision and how behavioural and other factors influence the decision making of an investor. Behavioural factors primarily include behavioural biases and personal characteristics of an investor, that is, personality, attitude, risk tolerance, and demographic factors, while other factors include external contextual factors like accounting information, market situations, brand image, and so forth, which have a bearing on decision making. The present paper provides an in-depth review of literature of prominent studies in the area of behavioural finance. The first part of the paper explains the concept of behavioral finance, the second part gives a detailed discussion on the classification of behavioural biases, and the third part discusses the effect of behavioural biases on the trading behaviour of the investors and the feelings of investors after experiencing the outcomes of investment. Towards the end, a comprehensive framework has been formulated representing the influence of behavioural biases on investment behaviour of an investor. The paper concludes that behavioural biases play a significant role in the decision making of the investors, and these biases not only shape the current investment decisions, but also influence investors’ future decision making.